2015
DOI: 10.1039/c4ra11537f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of POSS compounds and phosphorous hardeners on thermal and fire resistance of nanofilled aeronautic resins

Abstract: The aim of this work is the identification of the best strategy for improving thermal, fire resistance and electrical conductivity of an epoxy resin for aeronautic applications. The effect of DodecaPhenyl POSS (DPHPOSS), Epoxycyclohexyl POSS (ECPOSS), Glycidyl POSS (GPOSS) and TriglycidylCyclohexyl POSS (TCPOSS) to act as flame retardants of the resin was evaluated. Flame retardancy tested by the limiting oxygen index (LOI) indicated that GPOSS has meaningful effects on the flame retardancy of the epoxy mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 29 publications
0
77
0
Order By: Relevance
“…The selected MWCNT concentration was of 0.5% (by wt). 4 The GPOSS compound was dispersed at a percentage of 5 wt% in the epoxy matrix. 18 An ultrasonication for 20 min has been used in order to achieve a uniform dispersion of 0.5% (by wt) MWCNTs within the epoxy matrix.…”
Section: A T E R I a L S A N D S P E C I M E N Smentioning
confidence: 99%
See 2 more Smart Citations
“…The selected MWCNT concentration was of 0.5% (by wt). 4 The GPOSS compound was dispersed at a percentage of 5 wt% in the epoxy matrix. 18 An ultrasonication for 20 min has been used in order to achieve a uniform dispersion of 0.5% (by wt) MWCNTs within the epoxy matrix.…”
Section: A T E R I a L S A N D S P E C I M E N Smentioning
confidence: 99%
“…Multi walled carbon nanotubes (MWCNTs) and polyhedral oligomeric silsesquioxanes (POSS) are common additives to produce polymers with improved electrical conductivity as well as fire resistance [1][2][3][4] ; both features are very important for the aircraft structures as well as for several applications where safety is a concern, as boats, offshore, etc. Multi walled carbon nanotubes (MWCNTs) and polyhedral oligomeric silsesquioxanes (POSS) are common additives to produce polymers with improved electrical conductivity as well as fire resistance [1][2][3][4] ; both features are very important for the aircraft structures as well as for several applications where safety is a concern, as boats, offshore, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many eco-friendly flame retardants have been developed to improve the flame retardancy of EP, involving phosphorous-, nitrogen-, silicon-, phosphorous-/nitrogen-containing compounds and inorganic nanofillers (montmorillonite and aluminum hydroxide et al) [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the PLA/POSS composites were prepared and modulus and elongation at break values improved at low (1% and 3%) POSS loading levels [10]. Raimondo et al has reported that incorporation of 5 wt% of glycidyl POSS into the epoxy matrix resulted in a limiting oxygen index value of 33 with respect to 27 of the pure epoxy mixture [11] .…”
Section: Introductionmentioning
confidence: 99%